1995
DOI: 10.1007/bf02747291
|View full text |Cite
|
Sign up to set email alerts
|

Weldability and weld joint failures

Abstract: Welding plays a prominent role in the fabrication and erection of structures and components in the industry. Weld failures when they do occur, either during fabrication or service, involve considerable rework, apart from production, time and material losses. Hence, it is essential to adopt appropriate welding procedures depending on the material, weld configuration and the service requirement. In addition, the weldability of the material should be established with adequate laboratory tests in order to minimise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…[7,8] AF was first found in steel welds as laths that nucleate heterogeneously on small nonmetallic inclusions and grow in many different directions from these point nucleation sites. [9,10] Based on extensive investigations on the nature of AF, [11][12][13][14][15][16] it was found that the transformation mechanism of AF in steel welds is similar to that of bainite, except for the requirement of intragranular inclusions for AF nucleation. Therefore, AF in steel welds has been known as intragranularly nucleated bainite.…”
Section: Introductionmentioning
confidence: 99%
“…[7,8] AF was first found in steel welds as laths that nucleate heterogeneously on small nonmetallic inclusions and grow in many different directions from these point nucleation sites. [9,10] Based on extensive investigations on the nature of AF, [11][12][13][14][15][16] it was found that the transformation mechanism of AF in steel welds is similar to that of bainite, except for the requirement of intragranular inclusions for AF nucleation. Therefore, AF in steel welds has been known as intragranularly nucleated bainite.…”
Section: Introductionmentioning
confidence: 99%
“…[4,7] Through the elimination of welded joints, HIP can produce components exhibiting homogenous metallurgy; omitting common issues associated with problematic welded components such as hot cracking, heat-affected zones, and induced residual stresses. [8][9][10] The lack of heat-affected zones and lower residual stresses as a result of the HIP diffusion bonding could enhance resistance to environmentally assisted cracking (EAC). [11,12] Furthermore, the ability to completely avoid welding and subsequent machining not only reduces production lead times, costs, and volume of wasted material, but also eliminates significant expenses associated with costly manufacture and through-life weld inspection procedures.…”
Section: Introductionmentioning
confidence: 99%